An overview on plasticized biodegradable corn starch-based films: the physicochemical properties and gelatinization process. Issue 10 (31st March 2022) - Wang, Bin; Yu, Bin; Yuan, Chao; Guo, Li; Liu, Pengfei; Gao, Wei; Li, Dapeng; Cui, Bo; Abd El-Aty, A. M.
Abstract: With increasing awareness of environmental protection, petroleum-based raw materials are continuously decreasing, which in turn necessitated the development of eco-friendly sustainable biomaterials, as alternative strategy. Starch could be an ideal substitute. Corn starch has been used as a renewable material for development of biodegradable packaging, owing to great varieties, low cost, large-scale industrial production, and good films forming properties. Unfortunately, its poor mechanical and barrier properties have limited the application of starch-based films. Thence, plasticizers were added to overcome the aforementioned pitfalls and improve the films elongation, distribution, flexibility, elasticity, and rigidity. Addition of plasticizers can change the continuity and therefore would enhance the properties of corn starch-based films. While plasticization can improve the tensile strength and percent elongation, it can reduce the water resistance in prepared films. Herein, we focused on changes of starch granules during gelatinization process, types of biodegradable films, as well as the types of modified starch with plasticizers. Furthermore, the influence of plasticizers on corn starch-based films and the physicochemical properties of various types of corn starch-based films were also addressed.